Toxic Stress in Children. Issue 1 (January 2019) - Beal, Judy A.
Abstract : The recent controversy over the policy on immigration and subsequent treatment of immigrant children has resurfaced concerns about toxic stress in children. Our pediatric nursing expert, Dr. Beal, explains the clinical implications for children and the role of the nurse.